Case Report: Adrenal glands degenerated schwannoma: Report of three cases and literature review - Zhang, Tao; Yin, Si-fan; Feng, Wen-bo; Feng, Run-lin; Ke, Chang-xing (Frontiers in Oncology, 2023)
Schwannoma is a benign tumor, of which degenerated schwannoma is a subtype. Retroperitoneal schwannomas are extremely rare, as they account for only 3% of retroperitoneal tumors.Degenerated schwannoma is a schwannoma subtype. However,degenerated schwannoma occurring in the adrenal glands is extremely rare.